Plan estratégico para optimizar los servicios de comercialización de la empresa importadora Alonzo, cantón El Empalme, período 2014-2017 - Carreño Caicedo, Marianela Lisseth (2015)
This thesis aims to design a strategic plan that optimizes management and marketing company "IMPORTADORA ALONZO" period 2014-2017, and thus help to improve their planning. The following research is given to know the basics of the elements involved in developing a strategic plan and the benefits it provides when implemented in the company. The results obtained were surveys completed by the policy, administrative and enterprise customers part which helped identify SWOT, determining how strong the geographic location of the business as a weakness the lack of advertising such as population growth opportunity and a threat of competition, according to SWOT strategies to meet goals, programs and projects carried out were developed, it was also determined that strategic planning will help continuously improve the administrative management of the company. Inductive, deductive, analytic and synthetic methods are applied, the techniques used were direct observation and survey, and concluded that a strategic plan is vital for business success of any organization...